2019
DOI: 10.1177/0379572119826464
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Associated Factors Among University Students

Abstract: Background: Food insecurity is a growing public health issue and a barrier to students achieving adequate nutrition. Data regarding food insecurity among university students in Nigeria are scarce. Objective: The study assessed the prevalence of food insecurity and associated factors among university students, southeast Nigeria. Methods: A cross-sectional survey of 398 randomly selected students recruited from 2 universities in southeast Nigeria was conducted. Food security status was assessed using the 10-item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…In this study, occupation of the mother was a predictor of food security, this concurs with the study conducted in the Southeast, Nigeria [12] and Ethiopia [49]. Mother's occupation was associated with food secured level compared to very low food secured level as mothers who earn a salary are better able to manage the household, thereby reducing the level of food insecurity among adolescent girls.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, occupation of the mother was a predictor of food security, this concurs with the study conducted in the Southeast, Nigeria [12] and Ethiopia [49]. Mother's occupation was associated with food secured level compared to very low food secured level as mothers who earn a salary are better able to manage the household, thereby reducing the level of food insecurity among adolescent girls.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that more than half of respondents (73.5%) were in a very low food security level presented in Table 2 , this was higher than research conducted in Canada [ 37 ], Dhaka city [ 7 ], Southeast, Nigeria [ 12 , 38 ], Ethiopia [ 39 ], Boston [ 40 ], Ethiopia [ 41 , 42 , 43 ], Australia [ 44 ], and the U.S. [ 45 ]. The differences in the outcome of the study may be due to the humanitarian crisis experienced by the region from 2009 to date that has led to the displacement of people from their homes and farmlands.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Household food insecurity was also associated with educational status, with similar findings in three other studies [22,24,25]. This study indicated that food insecurity was higher among those respondents whose husbands were farmers and that is in line with the study of Ukegbu et al who found that food insecurity was higher among farmer headed households [26].…”
Section: Discussionsupporting
confidence: 90%
“…For university students, food choice and food consumption are determined by taste, health, and economic reasons (Ukegbu et al, 2019). This group of people could be vulnerable regarding food because they are vulnerable to poor socioeconomic status, poor eating patterns, and undernutrition (Gallegos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%